(untitled) (Research, Society and Development, 2022)
This article analyzes the relationship between technology project management (GPT and economic profitability (RE) for the areas of financial risks with the aim of presenting a flexible model between both variables derived from performance indices and cognitive skills for the area of financial risks of a Mexican banking institution. This is through a quantitative method supported by a predictive econometric model of data obtained from 313 technological projects. The results show that the RE depends on the behavior of the dimensions of the GPT; considering the information taken for empirical verification based on the resulting sample and other data derived from the qualitative indicators.